Analyse Multidimensionnelle Des Facteurs D’intégration Des Tice: Etude De Cas À Travers Le Programme Genie Marocain - Benfaress, Samiha; Zaki, Moncef; Alami, Anouar (European Scientific Journal, ESJ, 2016)
This article focuses on the integration of ICT in high-school level within the framework of teaching of sciences of Life and Earth. The experimentation was conducted with a sample of 112 Moroccan teachers of the region of Fez - Boulemane, who responded to a questionnaire of 16 modalities relating to the availability and the use of ICT tools, educational management of ICT in classroom, and the trainings and competencies in ICT and Informatics of the teachers. In order to make an original contribution to the study of the integration of ICT, we adopted a multidimensional analysis in the treatment of the answers of the teachers. Thus, thanks to a Factorial Analysis of Multiple Correspondence (FAMC), we could take account of the links which exist between the various modalities of our questionnaire to get to identify the most discriminating factors in the integration of ICT, like their order of importance. The results of this analysis led to three factorial axes cumulating an absolute inertia of 70%, respectively representing «the pedagogical contribution and the fundamental conditions of a success of the integration of ICT», «the advanced competencies in ICT and Informatics» and «the difficulties of use of ICT in classroom». These axes, in this hierarchy, represent finally the most discriminating factors for a successful integration of ICT.